PENGARUH BATANG FERRIT DAN BATANG CARBON TERHADAP PERFORMA MICROBIAL FUEL CELL DENGAN PIEZOELECTRIC MENGGUNAKAN LIMBAH TAHU CAIR - Saputro, Eko (RING ME, 2022)
One of the technologies currently being developed is Microbial Fuel Cell technology, namely the development of Microbial Fuel Cell technology using the bio-catalic activity of microorganisms. The addition of piezoelectric to the Microbial Fuel Cell to improve the performance of the electricity generated is greater. This study aims to determine the effect of ferrite rods and carbon rods on the performance of piezoelectric microbial fuel cells using liquid tofu waste. The method used is the experimental method. This method will examine the effect of variations in ferrite rods and carbon rods on the performance of piezoelectric microbial fuel cells using liquid tofu waste. In this study, it was found that the variation of the carbon rod electrode gave a better effect on the performance of the Microbial Fuel Cell reactor. Where the electricity produced is greater than the ferrite rod electrode. The results showed that the piezoelectric carbon rod electrode produced a maximum voltage of 117.96 mV at 72 hours. The voltage value affects other parameters so as to produce a maximum current of 0.118 mA, a maximum cell efficiency of 7.96%, and a maximum cell power of 8933.98 mW at the same hour